2019
DOI: 10.2147/amep.s146451
|View full text |Cite
|
Sign up to set email alerts
|

<p>Use of an online medical database for clinical decision-making processes: assessment of knowledge, attitude, and practice of oral health care providers</p>

Abstract: Purpose: This study was conducted to determine the level of knowledge, attitude, and practice of oral health care providers toward the use of online medical databases for clinical decision-making processes. Subjects and methods: The study population included all the licensed oral health care providers living in Rwanda, registered either with the Rwanda Allied Health Professional Council (RAHPC) or Rwanda Medical and Dental Council (RMDC). A self-administered questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 24 publications
0
22
0
2
Order By: Relevance
“…Among those that used EHIRs, their main reasonswere updating their knowledge (53.4%), clinical care of patients (28.8%), and supporting clinical decisions (14.4%). This result is in some context supported by the study conducted in the teaching hospitals of Isfahan University of Medical Science (health professionals used EHIRs to obtain new and updated information, supporting patients, and conducting research), 8 another conducted in Rwanda (used for supporting clinical decision-making, 34.8% for clinical procedure information), 17 and one in Nigeria (used for accessing patient-care information, research purposes,…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Among those that used EHIRs, their main reasonswere updating their knowledge (53.4%), clinical care of patients (28.8%), and supporting clinical decisions (14.4%). This result is in some context supported by the study conducted in the teaching hospitals of Isfahan University of Medical Science (health professionals used EHIRs to obtain new and updated information, supporting patients, and conducting research), 8 another conducted in Rwanda (used for supporting clinical decision-making, 34.8% for clinical procedure information), 17 and one in Nigeria (used for accessing patient-care information, research purposes,…”
Section: Discussionmentioning
confidence: 79%
“…This study revealed that 70.8% of the health professionals utilized EHIRs, which is consistent with a study conducted in Saudi Arabia (72.7%), 20 and one in Iran (65.4%). 8 On the other hand, this result is lower than a study conducted in the UK (81%), 21 one in Rwanda (80%), 17 and another in Osun state, Nigeria (82.2%). 25 IT infrastructure has a key role in EHIR use,so this discrepancy might be due to differences in IT infrastructure among those study settings.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations